Enlargement versus deepening: the trade-off facing economic unions - Jens Oliver Lorz; Gerald Willmann (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyzes the relationship between the size of an economic union and the degree of policy centralization. We consider a political economy setting in which elected representatives bargain about the degree of centralization within the union. In our model strategic delegation affects the identity of the representatives and hence the equilibrium policy outcome. We show that the relationship between the size of the union and centralization may be non-monotonic: Up to a certain size of the union enlargement leads to deeper integration, whereas beyond that size further enlargement implies less centralization. We also show that freezing the level of centralization or allowing an associated membership can mitigate the trade-off.
Keywords: D78; H77; H87; 330; Fiscal federalism; policy centralization; political economy; Wirtschaftsunion; Zentralstaat; Föderalismus; Public Choice; Finanzföderalismus; Theorie